SPECTROSCOPIC METALLICITY DETERMINATIONS FOR W UMa-TYPE BINARY STARS - Rucinski, Slavek M.; Pribulla, Theodor; Budaj, Ján (The Astronomical journal, 2013)
This study is the first attempt to determine the metallicities of W UMa-type binary stars using spectroscopy. We analyzed about 4500 spectra collected at the David Dunlap Observatory. To circumvent problems caused by the extreme spectral line broadening and blending and by the relatively low quality of the data, all spectra were subject to the same broadening function (BF) processing to determine the combined line strength in the spectral window centered on the Mg I triplet between 5080 A and 5285 A. All individual integrated BFs were subsequently orbital-phase averaged to derive a single line-strength indicator for each star. The best defined results were obtained for an F-type sub-sample (0.32 < (B - V) sub(0) < 0.62) of 52 binaries for which integrated BF strengths could be interpolated in the model atmosphere predictions.